Kvinnor som minoritet inom Norrbottens flygflottilj : Jämställdhet och rekrytering inom F21 - Bergqvist, Diana (2015)
The Armed Forces are an important operator in the community and is one of Sweden's largest agency with about 51,517 employees, where 6,866 are women and 44,651 are men. In Sweden, the Armed management wants to change these unequal numbers and has compiled three aspects to expand the proportion of women in the swedish armed forces. It is essentially about a rights perspective, everyone should have equal opportunities to influence and participate in society and have access to power and influence. The second reason is that the armed forces want to be an attractive employer that will gain the entire population, ultimately the armed forces want to have increased operational effectiveness.The purpose of this study was to examine how the Swedish Air Force (F21) in Luleå work to recruit more women to the defensive forces, as well as how female employees experiencing their work in a male-dominated workplace. This study has a sociological point of view with Human resource management as perspective.The study is a qualitative case study with semi-structured interviews, where recruiters and staff women shared their experiences regarding recruitment, their experience working at F21 and marketing in F21.The results showed that, in a trial project, units collaborate in the north and work together to attract more women to apply for Swedish Armed Forces. Those who are responsible for this project are the National Defence College and Staff at Headquarters. The aim of the project is to develop improved methods for recruitment of specific target groups. It has been found that there are challenges in attracting women to the Swedish Armed Forces, even though female employees have increased. The reason why there are fewer women seeking to F21 in this study, is because the armed forces have been male-dominated for a long time and it is still the image that many women retain. Another reason is that the ancient norms and values remains in the organization, and these take a long time to change.The results show also that there is some ...